2020
DOI: 10.21873/invivo.11995
|View full text |Cite
|
Sign up to set email alerts
|

Volume Delineation in Cervical Cancer With T2 and Diffusion-weighted MRI: Agreement on Volumes Between Observers

Abstract: Aim: To delineate cervical cancer gross tumor volume (GTV) on T2-magnetic resonance imaging (MRI) and apparent diffusion coefficient (ADC) maps, assessing volumes and inter-observer agreement between two observers. Patients and Methods: A radiologist and a radiation oncologist delineated GTV on T2 (T2 GTV) and ADC (ADC GTV) sequences. Dice similarity index (DICE) and Bland-Altman analysis were used to estimated concordance. Results: Mean T2 GTV and ADC GTV volumes were 43.84±71.47 cc and 37.28±68.92 cc accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The fact that the similarity between delineation with or without DWI‐MRI, but both with PET/CT as the other metabolic image modality might indicate that the biological information provided by the two metabolic image modalities is similar. A similar conclusion was reach on a study regarding patients with cervical cancer that reported a good agreement between PET/CT and DWI‐MRI 43 . However, the fact that the highest DSC was reported only between PET/CT and CT alone might be explained by the fact that the observers in this study have classified DWI images as having a fair discrimination but an indistinct margin.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The fact that the similarity between delineation with or without DWI‐MRI, but both with PET/CT as the other metabolic image modality might indicate that the biological information provided by the two metabolic image modalities is similar. A similar conclusion was reach on a study regarding patients with cervical cancer that reported a good agreement between PET/CT and DWI‐MRI 43 . However, the fact that the highest DSC was reported only between PET/CT and CT alone might be explained by the fact that the observers in this study have classified DWI images as having a fair discrimination but an indistinct margin.…”
Section: Resultssupporting
confidence: 86%
“…A similar conclusion was reach on a study regarding patients with cervical cancer that reported a good agreement between PET/CT and DWI-MRI. 43 However, the fact that the highest DSC was reported only between PET/CT and CT alone might be explained by the fact that the observers in this study have classified DWI images as having a fair discrimination but an indistinct margin. Only 6% of the observers considered that DWI provided excellent discrimination and distinction of the tumor.…”
Section: Dice Similarity Coefficientmentioning
confidence: 63%
“…Studies comparing CTand MRI-guided contour delineation for IGABT have shown that tumour contours can be significantly overestimated on CT [56,70]. Other important advantages include the ability to use functional MRI to assess tumour response [63,71,72], with the potential for dose amendments to target radioresistant regions providing personalised oART [61,62,73].…”
Section: Magnetic Resonance Imaging-guided Online Adaptive Radiotherapymentioning
confidence: 99%
“…The requirements of fast pace and accurate planning will put the entire workflow under high pressure, thus increasing planning errors. Moreover, the planner's experience level and preferences would result in significant inter-and intra-observer variations [8,9], further introducing more uncertainties in treatment planning and dose delivery [10][11][12].…”
Section: Introductionmentioning
confidence: 99%